Det samtidige Regietheater af Pınar Karabulut og Christopher Rüping: Et dramaturgisk perspektiv på iscenesættelsen af litterære tekster - Boenisch, Peter M. (Passage - Tidsskrift for litteratur og kritik, 2025)
The Contemporary Regietheater of Pınar Karabulut and Christopher Rüping: A Dramaturgic Perspective on Stage Productions of Literary Texts The article analyses the works of these two prominent directors in contemporary German theatre. Their works do not simply illustrate nor interpret staged texts, but foreground resonances with present-day “structures of feeling”, thereby exemplarily displaying the complex relation between texts and their staging that is characteristic for the Regietheater-tradition.